Profil Infeksi Blastocystis sp. pada Penderita Karsinoma Kolorektal - Izzati, Ruhilda; Nofita, Eka; Suchitra, Avit; Rusjdi, Selfi Renita; Rustam, Rony; Meinapuri, Malinda (FORIKES, 2024)
Blastocystis sp. is one of the intestinal parasites that are often found in humans that cause digestive system disorders. Blastocystis sp. infection is thought to initiate the development of colorectal carcinoma because it induces inflammation in the gastrointestinal tract. This study aimed to determine the picture of Blastocystis sp. infection in colorectal carcinoma patients at Dr. M. Djamil Padang General Hospital. This study was a descriptive study, which was conducted at Dr. M. Djamil Padang General Hospital and the Parasitology Laboratory of the Faculty of Medicine, Andalas University with a sample size of 47 patients with colorectal carcinoma, who were selected using consecutive sampling techniques. The incidence of Blastocystis sp. infection was determined by microscopic examination of feces. Data were analyzed descriptively in the form of frequency tables and percentages. The results showed the incidence of Blastocystis sp. infection. in patients with colorectal carcinoma was 19.1%, most of whom were male (77.8%), under 50 years of age (44.5%), and generally had loose stool consistency (66.7%). Furthermore, it was concluded that the incidence of Blastocystis sp. infection in patients with colorectal carcinoma was quite high.Keywords: Blastocystis sp. infection; colorectal carcinoma; stool examination ABSTRAK Blastocystis sp. merupakan salah satu parasit usus yang sering ditemukan pada manusia yang menimbulkan gangguan sistem pencernaan. Infeksi Blastocystis sp. diduga dapat menginisiasi berkembangnya karsinoma kolorektal karena menginduksi inflamasi pada traktus gastrointestinal. Penelitian ini bertujuan untuk mengetahui gambaran infeksi Blastocystis sp. pada penderita karsinoma kolorektal di RSUP Dr. M. Djamil Padang. Penelitian ini adalah studi deskriptif, yang dilaksanakan di RSUP Dr. M. Djamil Padang dan Laboratorium Parasitologi Fakultas Kedokteran Universitas Andalas dengan ukuran sampel 47 pasien dengan karsinoma kolorektal, yang diseleksi dengan teknik consecutive sampling. Kejadian infeksi Blastocystis sp. Ditentukan dengan pemeriksaan tinja secara mikroskopis. Data dianalisis secara deskriptif berupa tabel frekuensi dan persentase. Hasil penelitian menunjukkan angka kejadian infeksi Blastocystis sp. pada penderita karsinoma kolorektal adalah 19,1%, yang sebagian besar berjenis kelamin laki-laki (77,8%), berusia di bawah 50 tahun (44,5%), dan konsistensi tinja umumnya encer (66,7%). Selanjutnya disimpulkan bahwa kejadian infeksi Blastocystis sp. pada pasien dengan karsinoma kolorektal cukup tinggi.Kata kunci: infeksi Blastocystis sp.; karsinoma kolorektal; pemeriksaan tinja